1988
DOI: 10.3109/01902148809062847
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Phosphatidylcholines in Ozone-Exposed Alveolar Type II Cells Isolated from Adult Rat Lung: Is Glycerolphosphate Acyltransferase a Rate-Limiting Enzyme?

Abstract: Type II cells were exposed to ozone by gas diffusion through the thin Teflon bottom of culture dishes. The rate of phosphatidylcholine synthesis by type II cells, monitored by the incorporation of [Me-14C]choline, was impaired by ozone at concentrations that did not affect other cellular parameters. The enzymes choline kinase and cholinephosphate cytidylyltransferase were not susceptible to inactivation by ozone at concentrations at which the activity of glycerolphosphate acyltransferase was decreased. The enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Adult type II cells may be different from other cells because of their exceptionally high rate of uptake and choline phosphorylation and their high rate of PC synthesis, even at low substrate concentration (22). In our experiments, the rate of PC synthesis from [Me-14 C]choline appeared to be sensitive to ZD because the radioactivity increased 12% in PC, but in SPH it decreased 73% in relation to the control group (Fig.…”
Section: Table 4 Phospholipid Composition Of Whole Lung and Subcellulmentioning
confidence: 53%
See 1 more Smart Citation
“…Adult type II cells may be different from other cells because of their exceptionally high rate of uptake and choline phosphorylation and their high rate of PC synthesis, even at low substrate concentration (22). In our experiments, the rate of PC synthesis from [Me-14 C]choline appeared to be sensitive to ZD because the radioactivity increased 12% in PC, but in SPH it decreased 73% in relation to the control group (Fig.…”
Section: Table 4 Phospholipid Composition Of Whole Lung and Subcellulmentioning
confidence: 53%
“…CTP:cholinephosphate CYT assay. Lungs of control and zinc-deficient rats were used for the separation of cytosol and microsomes for enzymatic determination (22). Assay mixtures contained 20 mM Tris/succinate pH 7.8, 6 mM MgCl 2 , 8mM CTP, and 4 mM [Me-14 C]phosphorylcholine (specific radioactivity 1 µCi/assay).…”
Section: Chemicalsmentioning
confidence: 99%
“…Este último leva à produção de radicais hidroxil, altamente reactivos. A enzima glicerol-3-fosfatase acetiltransferase, que catalisa a primeira reacção na síntese de todos os fosfoglicerídeos necessários para a formação de surfactante, é extremamente sensível ao stress oxidativo 60 . Todos estes eventos afectam o sistema de produção e de funcionamento do surfactante, com compromisso da função pulmonar e diminuição da resistência à infecção 58 .…”
Section: No Recém-nascido De Pré-termo Os Processos Pró-oxidantes Sãunclassified
“…It was shown that incorporation of a number of precursors into PC was clearly reduced after O 3 . In parallel it was found that the activity of the glycerol‐3‐phosphate acyltransferase, which catalyses the first reaction in phosphoglyceride synthesis, was significantly decreased, whereas other enzymes remained unaltered [ 124, 125]. Also, after exposure to 100% hyperoxia (64 h), the activity of this enzyme was decreased.…”
Section: Toxicitymentioning
confidence: 99%